Kesadaran Masyarakat Dalam Memahami Undang Undang Nomor 11 Tahun 2008 Tentang Informasi Transaksi Elektronik Dalam Media Sosial - Sardjana Orba Manullang (Adiba Aisha Amira, 2022)
Cultivating the habit of being aware of the law is the responsibility of all parties, even more so for educational institutions. Educational institutions are primary socialization media that greatly influence the formation of human character in the future. If the attitude and behavior of obeying the law has been instilled from an early age, then in the future, the attitude to respect and obey the rules will be ingrained and entrenched in society. Of course this is done by providing correct knowledge about what not to do and what to do.